Efektifitas mendengarkan asmaul husna terhadap penurunan nyeri kepala pada pasien cedera kepala - -, Afrianti -; Utami, Gamya Tri; Utami, Sri - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The research purpose was to know  the effectivity of listening Asmaul husna in decreasing head pain scale to patient with head injury. This research used “quasi exsperimental” method with rendomired pre and post test control design. The amount of sample is 30 people using purposive sampling technique, considering inclusive criteria the sample are devided in to two group experimental and control group. The measuring tools was observation sheet, describing pain scale from 0 to 10. The experimental and control data were analyzed by wilxocon test, while the influenceof  Asmaul husna to head pain was analyzed by T Independent test. The result show that there was a significance different between the experiment and control group with p=0,000(p<0,05), it is indicate that the distraction technique by listening Asmaul husna was effective in decreasing  head pain scale.Based on this research that nurse or expected to be health worker are able to apply the intervention of listening Asmaul husna in caring patient who suffer with head injury. Keywords: Asmaul Husna, pain, head injuries.